2022
DOI: 10.3389/fpls.2022.993130
|View full text |Cite
|
Sign up to set email alerts
|

Plant-endophyte mediated improvement in physiological and bio-protective abilities of marigold (Tagetes patula)

Abstract: Endophytic bacteria improve the growth, physiology, and metabolite profile of plants. They are known as potential biocontrol agents of soil-borne diseases. This study evaluated the effects of endophytic bacterial strains on growth, vase life, biochemical attributes, and antioxidant and nematicidal activities of French marigold (Tagetes patula). French marigold seeds were sole and consortium inoculated with three promising endophytic bacterial strains, Burkholderia phytofirmans (PsJN), Enterobacter sp. (MN17), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…The high halotolerance among the endophytes themselves for plants growing in a salty environment suggests that the plant can more easily adapt to stress along with different bacterial populations [ 17 , 18 ]. Therefore, endophytic bacteria can be used as biofertilizers, alleviating salt stresses due to their direct interaction with the host plant, leading to less competition with other microbes [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The high halotolerance among the endophytes themselves for plants growing in a salty environment suggests that the plant can more easily adapt to stress along with different bacterial populations [ 17 , 18 ]. Therefore, endophytic bacteria can be used as biofertilizers, alleviating salt stresses due to their direct interaction with the host plant, leading to less competition with other microbes [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The significant impact of endophytes on the defense response of host plants against pathogens might be through early detection of pathogens by host plant cell surface receptor kinases, through cytoplasmic kinase-mediated intercellular responses, and by triggering of ethylene and jasmonic acid transduction pathways [ 24 , 50 ]. Zhao et al [ 50 ] and Naveed et al [ 51 ] reported the enhanced shoot and root growth, fresh and dry weight, and chlorophyll, phenol, protein, and cellulose contents of tissues, in endophytic microbe-inoculated plants. More detailed studies to unveil the exact mechanism via which endophytes antagonize Xap pathogen are required in future.…”
Section: Discussionmentioning
confidence: 99%
“…(Saffron crocus) [65] Polyphenols Liquiritin Rhodoplanes Roots Glycyrrhiza uralensis Fisch [52] * Liquiritin Bacillus amyloliquefaciens FZB42 Roots Glycyrrhiza uralensis Fisch [55] Calycosin-7-glucoside Phyllobacterium Inquilnus Roots Astragalus mongholicus [59] * Kaempferol-7-O-glucoside Kaempferol3,7-di-O-glucoside Ruminococcaceae bacterium GD7 Roots Paeonia lactiflora Pall [71] * Flavonoids Ruminococcaceae Leaves Ginkgo biloba [73] * Piceatannol, kyotorphin Burkholderia ambifaria LK-P4 Leaves Anoectochilus roxburghii [75] Flavonoids, total polyphenols Bacteria consortium Flowers Tagetes patula L . (French marigold) [76] Alkannin/shikonin Labrys Allorhizobium-Neorhizobium-Pararhizobium-Rhizobium Penicillium (fungus) Roots Alkanna tinctoria L . [77] * Alkannin/shikonin Chitinophaga sp.…”
Section: Microbe-increased Production Of Terpenoidsmentioning
confidence: 99%
“…In Anoectochilus roxburghii that produces kyotorphin and piceatannol, the bacteria treatment with Burkholderia ambifaria LK-P4 increased the plant contents of these two phenolic compounds, which can significantly decrease blood glucose levels and protect the organs of mice with similar effects of glibenclamide tablet, a standard drug for the symptomatic treatment of diabetic mice [75] . In French marigold ( Tagetes patula L.) that is used for skin and digestive conditions, the treatment of an endophytic bacteria consortium resulted in 56 % and 38 % in the contents of flavonoids and total polyphenols, respectively [76] .…”
Section: Microbe-increased Production Of Polyphenolsmentioning
confidence: 99%